Advancing African otolaryngology and head & neck surgery education and training through virtual academic platforms and multidisciplinary teams. Issue 3 (June 2021) - Din, Taseer F.; Macharia, Chege; Harris, Tashneem
Abstract : Purpose of review: To overview the rise of virtual tools to propagate academia and clinical service within Africa, in the field of otolaryngology, propelled by the coronavirus disease 2019 (COVID-19) pandemic. Recent findings: The rise of the COVID-19 virus saw a dramatic reduction in elective surgery and outpatient services with a subsequent reduction in experiential learning for trainees. This has spurred the rising trend to maintain the mission of education and clinical service, virtually. There have been unprecedented levels of international collaboration in the 'pandemic year of 2020' that has seen various platforms conceived to harmonize varying practices from global experts towards the ultimate goal of education propagation and improved patient care. The continent of Africa, amidst its own unique challenges, has boldly stepped into the virtual realm in form of a resident-centred platform coined University Of Cape Town-Africa Virtual ENT, and two multidisciplinary team (MDT) meetings: the African Head and Neck Society Virtual Tumour Board and the African Virtual Cochlear Implant Meeting. Summary: The COVID-19 pandemic will have long-lasting effects on clinical practice and training programs globally. This has demanded academicians to re-imagine novel ways to buoy academia and maintain international collaboration in an inexpensive and convenient way to nourish the sacred mission of education and clinical service within our spirited continent.